The Efficacy of Mesenchymal Stem Cell Transplantation in Caustic Esophagus Injury: An Experimental Study. (4th May 2014) - Kantarcioglu, Murat; Caliskan, Bahadir; Demirci, Hakan; Karacalioglu, Ozgur; Kekilli, Murat; Polat, Zulfikar; Gunal, Armagan; Akinci, Melih; Uysal, Cagri; Eksert, Sami; Gurel, Hasan; Celebi, Gurkan; et al.
Abstract : Introduction. Ingestion of corrosive substances may lead to stricture formation in esophagus as a late complication. Full thickness injury seems to exterminate tissue stem cells of esophagus. Mesenchymal stem cells (MSCs) can differentiate into specific cell lineages and have the capacity of homing in sites of injury. Aim and Methods. We aimed to investigate the efficacy of MSC transplantation, on prevention of esophageal damage and stricture formation after caustic esophagus injury in rats. 54 rats were allocated into four groups; 4 rats were sacrificed for MSC production. Group 1, untreated controls (n : 10). Group 2, membrane labeled MSCs-treated rats (n : 20). Group 3, biodistribution of fluorodeoxyglucose labeled MSCs via positron emission tomography (PET) imaging (n : 10). Group 4, sham operated (n : 10). Standard caustic esophageal burns were created and MSCs were transplanted 24 hours after. All rats were sacrificed at the 21st days. Results. PET scan images revealed the homing behavior of MSCs to the injury site. The histopathology damage score was not significantly different from controls. However, we demonstrated Dil labeled epithelial and muscle cells which were originating from transplanted MSCs. Conclusion. MSC transplantation after caustic esophageal injury may be a helpful treatment modality; however, probably repeated infusions are needed.